2020
DOI: 10.1186/s13000-020-00951-x
|View full text |Cite
|
Sign up to set email alerts
|

IGF2BP3 (IMP3) expression in angiosarcoma, epithelioid hemangioendothelioma, and benign vascular lesions

Abstract: Background: Insulin-like growth factor-2 messenger RNA-binding protein 3 (IGF2BP3 or IMP3) is an oncofetal protein that is expressed in various cancer types, and its expression is often associated with poor prognosis. IGF2BP3 expression has not been fully settled in vascular lesions. Methods: We evaluated the expression of IGF2BP3 in malignant (angiosarcoma and epithelioid hemangioendothelioma [EHE]) and benign (hemangioma, granulation tissue cappilaries, and pyogenic granuloma) vascular lesions using immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 20 publications
(34 reference statements)
0
7
0
Order By: Relevance
“…In the present study, the majority of lymphoma cells expressed IMP3 in all 25 SBs from patients with IVL. It has been reported that IMP3 is partially expressed in non‐neoplastic inflammatory cells and benign skin tumors 6,8 . However, none of the 27 SBs from patients without IVL harbored intravascular IMP3‐positive B‐cells.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…In the present study, the majority of lymphoma cells expressed IMP3 in all 25 SBs from patients with IVL. It has been reported that IMP3 is partially expressed in non‐neoplastic inflammatory cells and benign skin tumors 6,8 . However, none of the 27 SBs from patients without IVL harbored intravascular IMP3‐positive B‐cells.…”
Section: Figurementioning
confidence: 95%
“…It has been reported that IMP3 is partially expressed in non-neoplastic inflammatory cells and benign skin tumors. 6,8 However, none of the 27 SBs from patients without IVL harbored intravascular IMP3-positive B-cells.…”
mentioning
confidence: 99%
“…In the screening for m6A-related proteins, only IGF2BP3 was found to be related to RA; therefore, we theorized that it was a crucial factor influencing RA-related m6a methylation. IGF2BP3, one of the readers of m6A methylation, has been shown to play a regulatory role in many diseases including cancer ( 40 42 ) and cardiovascular diseases ( 43 , 44 ); however, its role in RA is unknown. In this study, we found that IGF2BP3 is mainly involved in the regulation of inflammation-related pathways, including the MAPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to further determine whether or not a direct interaction between IMP3 and VEGF mRNA IMP3, also known as insulin-like growth factor 2 (IGF2) mRNAbinding protein 3 (IGF2BP3), is a member of the insulin-like growth factor 2 mRNA-binding proteins family. [28][29][30] IMPs play its role in post-translational RNA processing, such as transcript localization, translation and stabilization [31][32][33] ; additionally, IMPs family were recently identified as a family of m6A readers. 8,34 However, previous research mainly focussed on the biological functions of IMPs in tumours and embryogenesis.…”
Section: Imp3 As Rna-binding Protein Increases the Stability Of Vegf ...mentioning
confidence: 99%